A set of almost periodic discontinuous functions - Díaz, Lolimar; Naulin, Raúl (Pontificia Universidad Católica del Perú, 2006)
In this paper the non density of AP, the set of almost periodic functions in the sense of Bohr, in the space S of almost periodic functions in the sense of Stepanov is proven.
Keywords: Bohr And Stepanov Almost Periodic Functions; Almost Periodic Sequences; https://purl.org/pe-repo/ocde/ford#1.01.00